Sustainable use of natural resources for crop intensification and better livelihoods in the rainfed semi-arid tropics of Central India. (1st September 2016) - Wani, Suhas P.; Chander, Girish; Sahrawat, Kanwar L.; Pal, D.K.; Pathak, P.; Pardhasaradhi, G.; Kamadi, P.J.
Highlights: Soils in Central India are widely degraded in micro and macro nutrients. Balanced fertilization is a scalable option for sustainable intensification. Cultivating rainy fallows in Vertisols is an opportunity to boost food production. Landform and soil fertility management are twin technologies to cultivate rainy fallows. Abstract: In Indian semi-arid tropics (SAT) in general and central part i.e. Madhya Pradesh state specifically; there are large yield gaps in most of the rainfed crops between current farmers' yields and achievable ones. Soil fertility related degradation due to deficiencies of secondary and micronutrients mainly sulphur, boron and zinc in addition to macronutrients is mainly responsible for poor crop productivity, and along with poor hydraulic properties of Vertisols is responsible for about 2 million ha rainy season fallows. Soil health assessment of 11 districts in Madhya Pradesh, India has revealed that in most of the districts only few fields with adequate levels of sulphur, boron, zinc and phosphorus indicating their widespread low levels. Potassium was in general adequate. Farmers' current blanket fertilization practices focused at macronutrients viz. nitrogen, phosphorus and potassium only, thus does not meet the variable soil fertility needs. Through participatory action research on soil test based fertilizer application, farmers realized benefits in crop productivity to the tune of 5 to 45% in the season of application and additional yield by 5 to 27% due to residual effects of S, B and Zn in succeeding three seasons. An economic assessment showed the balanced nutrition a profitable option in the 1 st season itself. In current rainy fallow regions, the landform management as broadbed and furrow or conservation furrow along with balanced nutrition has shown that fallow lands in black soil regions in Madhya Pradesh can be successfully cultivated to grow soybean crop. In succeeding post-rainy season, the rainy season cultivated plots also yielded more as compared to adjoining plots having one crop only in post-rainy season. This study thus found that soil test based fertilization and landform management are the twin technologies for sustainable crop intensification in black soils of Central Indian region.